(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
Decapitation deaths cases are not seen commonly and always set a challenge to forensic pathologist and investigation officer about their modes of death. Meticulous postmortem examination, scientific approach and necessary laboratory investigation are need of hour to solve mysteries and to address bewildering issues of decapitation deaths. Three cases of different nature and modes are discussed here.